Association between depression and BMI in young adults - Wang, Haoshuang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Globally, depression significantly affecting people’s quality of life with a range of negative health outcomes. Previous studies have confirmed a link between BMI and depression. Consequently, this study focused on data spanning from 2017 to March 2020, encompassing individuals aged 18 to 30 years within the National Health and Nutrition Examination Survey (NHANES). The study included 1635 participants, with complete data and selected covariates. Then, used weighted logistic regression models to investigate the connection between depression and BMI. Given the significant influence of gender, subgroup analysis was performed to compare the varying impact of BMI between males and females. Ultimately, the analysis of model results revealed a noteworthy positive correlation between BMI and depression within the 18-30 age group, with women experiencing a more pronounced effect than men. In conclusion, reducing BMI emerges as a potential strategy to mitigate the risk of depression.